The Preparation of Strategic Plans for Elementary School Students of Islamic Educational Institutions - Mesiono, Mesiono; Azmi, Fachruddin; Putra, Muhammad Irwansah; Rafiqah, Sri Rezeqi; Faisal, Faisal (Jurnal Basicedu, 2022)
The strategic plan is a form of madrasah effort in the orientation of achieving educational success. This study attempts to analyze the preparation of the strategic plan carried out by the Private Madrasah Ibtidaiyah (MIS) Kesuma LKMD Namorambe. This study uses a qualitative approach with descriptive analytical study method. Data collection was carried out using in-depth interview techniques, participant observation and document review. Furthermore, the data were analyzed using data sorting techniques according to relevance to the research theme, then presented in a qualitative format, and verified to draw conclusions. Test the validity of the data using the persistence of observation and data triangulation techniques. The results of this study conclude that first, the strategic plan (renstra) is used as the basis for the preparation of periodic (semester/annual) institutional programs based on the vision, mission, and goals of the madrasa. This is intended to clarify the details of program objectives, madrasah internal policies, and implementation strategies. Second, the strategic plan as the basis for program implementation at MIS Kesuma LKMD Namorambe. Third, the strategic plan has a close relationship (interrelated) with the operational plan in an effort to achieve the goals of the madrasa.